Evaluation of patients with stroke monitored by home care programs - Ana Railka de Souza Oliveira; Thelma Leite de Araujo; Alice Gabrielle de Sousa Costa; Huana Carolina Candido Morais; Viviane Martins da Silva; Marcos Venicios de Oliveira Lopes (SciELO, 2013)
The purpose of this study was to evaluate the patient with a stroke in home treatment, investigating physical capacity, mental status and anthropometric analysis. This was a cross-sectional study conducted in Fortaleza/CE, from January to April of 2010. Sixty-one individuals monitored by a home care program of three tertiary hospitals were investigated, through interviews and the application of scales. The majority of individuals encountered were female (59%), elderly, bedridden, with a low educational level, a history of other stroke, a high degree of dependence for basic (73.8%) and instrumental (80.3 %) activities of daily living, and a low cognitive level (95.1%). Individuals also presented with tracheostomy, gastric feeding and urinary catheter, difficulty hearing, speaking, chewing, swallowing, and those making daily use of various medications. It was concluded that home care by nurses is an alternative for care of those individuals with a stroke.